2017
DOI: 10.20333/2500136-2017-2-84-90
|View full text |Cite
|
Sign up to set email alerts
|

Influence Features of Cold and Heat Waves to the Population Mortality - The City With Sharply Continental Climate

Abstract: Цель исследования. Выбор наилучшего предиктора смертности во время волн жары и холода в условиях резко-континентального климата. Стратификация рисков смертности во время таких волн в Красноярске по основным причинам и возрастным группам для выявления основных температурных факторов повышенной смертности. Сравнение рисков с аналогичными результатами, полученными в южных городах России. Материал и методы. Метеоданные по 6 выбранным городам Сибири с резко-континентальным климатом получены с сайта Росгидромета. Дл… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 7 publications
1
12
0
1
Order By: Relevance
“…First, it was shown that heat (cold) waves were mainly defined as periods with abnormally high (low) temperatures compared to current values, often combined with high humidity (strong wind), which have an adverse effect on human body, expressed in a statistically significant increase in mortality or morbidity [69,71,72,[93][94][95][96][97][98][99][100][101][107][108][109][110][111]. Based on long-term research, it was determined that heat (cold) waves incorporate periods with an excess of the 97(3) % percentile of the distribution of mean daily temperature in the summer (winter) months [145,177].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…First, it was shown that heat (cold) waves were mainly defined as periods with abnormally high (low) temperatures compared to current values, often combined with high humidity (strong wind), which have an adverse effect on human body, expressed in a statistically significant increase in mortality or morbidity [69,71,72,[93][94][95][96][97][98][99][100][101][107][108][109][110][111]. Based on long-term research, it was determined that heat (cold) waves incorporate periods with an excess of the 97(3) % percentile of the distribution of mean daily temperature in the summer (winter) months [145,177].…”
Section: Resultsmentioning
confidence: 99%
“…When analyzing temperature waves, in addition to their duration, other indicators were described: the wave intensity, i.e. the sum of degrees above (below) the base temperature [72]; the "wave fraction" defined as the ratio of the number of days in the wave to the total number of days with temperatures above (below) the temperature threshold, for heat and cold waves, respectively [94,99]; the time shift between the beginning of the wave and the impact on the human body as the lagged effect [55,70,97,98,100,101]. In addition, increased (decreased) temperature background in summer (winter) [69,71,72,107] and air pollution [73,108] were analyzed, which contribute to the exacerbation of diseases during heat and cold waves.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations